2022
DOI: 10.1007/s10787-022-01080-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of berberine in Covid-19: potential adjunct therapy

Abstract: Coronavirus disease 2019 (Covid-19) is a global diastrophic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Covid-19 leads to inflammatory, immunological, and oxidative changes, by which SARS-CoV-2 leads to endothelial dysfunction (ED), acute lung injury (ALI), acute respiratory distress syndrome (ARDS), and multi-organ failure (MOF). Despite evidence illustrating that some drugs and vaccines effectively manage and prevent Covid-19, complementary herbal medicines are urgently ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…SARS-CoV-2 is a large genomic RNA virus with a genome size of 27–34 kb ( Al-Kuraishy et al, 2022a ). It primarily infects lung cells because they express angiotensin-converting enzyme 2 (ACE2) ( Babalghith et al, 2022 ). Middle East Respiratory Syndrome CoV (MERS-CoV), SARS-CoV, and SARS-CoV-2 share genetic similarities, though SARS-CoV-2 is less pathogenic and has a higher transmissibility rate than SARS-CoV ( Al-Kuraishy et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 is a large genomic RNA virus with a genome size of 27–34 kb ( Al-Kuraishy et al, 2022a ). It primarily infects lung cells because they express angiotensin-converting enzyme 2 (ACE2) ( Babalghith et al, 2022 ). Middle East Respiratory Syndrome CoV (MERS-CoV), SARS-CoV, and SARS-CoV-2 share genetic similarities, though SARS-CoV-2 is less pathogenic and has a higher transmissibility rate than SARS-CoV ( Al-Kuraishy et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…A current pandemic viral infection caused by severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2) leads to the progress of COVID‐19 48,49 . COVID‐19 is mainly asymptomatic in ~80% of infected patients.…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 99%
“…A current pandemic viral infection caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) leads to the progress of COVID-19. 48,49 COVID-19 is mainly asymptomatic in $80% of infected patients. Only 15% develop mild to moderate symptoms, including dry cough, myalgia, headache, anosmia, sweating and extrapulmonary symptoms like vomiting, diarrhoea, kidney impairment and CNS manifestations.…”
Section: Role Of Dantrolene In Severe Acute Respiratory Syndrome Coro...mentioning
confidence: 99%
“…It has been demonstrated that increasing bile acid production under high body temperature promotes the generation of chenodeoxycholic acid from gut microbiota. In addition, chenodeoxycholic acid limits SARS-CoV-2 proliferation and associated tissue injury in mice through activation of FXR (Babalghith et al 2022 ). Notably, through modulation of bile acid metabolism, gut microbiota provokes the stimulation of anti-inflammatory FXR (Hollman et al 2012 ; Zhang et al 2013 ) with following supression of the proliferation of the virus of Covid-19 (Spagnolello et al 2021 ).…”
Section: Fxr and Covid-19mentioning
confidence: 99%